2014
DOI: 10.1186/1756-0500-7-300
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of performance of Sri Lankan and US children on cognitive and motor scales of the Bayley scales of infant development

Abstract: BackgroundThere is no validated scale to assess neurodevelopment of infants and children in Sri Lanka. The Bayley III scales have used widely globally but it has not been validated for Sri Lankan children. We administered the Cognitive and Motor Scales of the Bayley III to 150 full-term children aged 6, 12 and 24 months from the Gampaha District of Sri Lanka. We compared the performance of Sri Lankan children 6, 12 and 24 months of age on the cognitive and motor scales of the Bayley III with that of US childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 8 publications
0
19
0
4
Order By: Relevance
“…51 However, Sri Lankan children had lower gross motor scores at 12 months. Compared with the BSITD-3 norms, Sri Lankan children demonstrated similar fine motor scores at 6 months, 12, and 24 months, and similar gross motor scores at 6 months and 24 months.…”
Section: Asia (Sri Lanka Taiwan)mentioning
confidence: 98%
See 4 more Smart Citations
“…51 However, Sri Lankan children had lower gross motor scores at 12 months. Compared with the BSITD-3 norms, Sri Lankan children demonstrated similar fine motor scores at 6 months, 12, and 24 months, and similar gross motor scores at 6 months and 24 months.…”
Section: Asia (Sri Lanka Taiwan)mentioning
confidence: 98%
“…Compared with the BSITD-3 norms, Sri Lankan children demonstrated similar fine motor scores at 6 months, 12, and 24 months, and similar gross motor scores at 6 months and 24 months. 51 However, Sri Lankan children had lower gross motor scores at 12 months. Given the small differences in motor scores found between Sri Lankan children and the BSITD-3 normative sample, Godamunne et al 51 concluded that it is feasible to use the BSITD-3 to assess the motor development of Sri Lankan children.…”
Section: Asia (Sri Lanka Taiwan)mentioning
confidence: 98%
See 3 more Smart Citations